From condemnation to normalisation: Young Africans' narratives about same-sex attraction and implications for communication and advocacy efforts. Issue 7 (3rd July 2018) - Winskell, Kate; Sabben, Gaëlle; Stephenson, Rob; Pruitt, Kaitlyn L.; Allen, Kristi; Findlay, Trinity
ABSTRACT: Narrative is a primary tool in human meaning-making and communication. Frequently value-laden, it plays an important role in global public health communication and advocacy efforts. State-endorsed homophobia is widespread across much of sub-Saharan Africa, severely restricting access to sexual health services and undermining human rights and mental health for sexual minorities. Young Africans' narratives about same-sex attraction (SSA) can both inform message framing and provide a source of creative ideas for communication and advocacy efforts. We conducted an analysis of 56 narratives about SSA submitted by young people aged 13–24 years from 10 African countries to a spring 2013 scriptwriting competition in response to a prompt inviting participants to 'Tell a story about someone who is attracted to people of the same sex.' We categorised the narratives across a spectrum of attitudinal perspectives vis-à-vis SSA and identified characteristics of each category, ranging from condemnation (including characterising SSA as satanic), through ambivalence (e.g. 'love the sinner, hate the sin'), to acceptance, activism (including petitioning for same-sex marriage), and normalisation. The texts shed light on potential message frames and cultural narratives that can be countered or leveraged in communication efforts to improve the health and human rights of sexual minority Africans.